2021
DOI: 10.1002/dev.22214
|View full text |Cite
|
Sign up to set email alerts
|

Taking a few deep breaths significantly reduces children's physiological arousal in everyday settings: Results of a preregistered video intervention

Abstract: This preregistered, randomized field experiment tested the effectiveness of a brief deep breathing intervention on children's concurrent physiological arousal in naturalistic settings (N = 342; M age = 7.48 years; 46% female; 53% Asian, 26% White; 21% other race/ethnicity). The treatment consisted of an animated video that introduced deep breathing as a self-regulation strategy and scaffolded the child in taking a few slow-paced breaths, while the control group watched an informational video featuring similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Deep breathing is a valuable skill that parents can teach their children to help them manage their emotions and facilitate an SRS for optimal EC. Using deep breathing connects well with previous studies on the significance of deep breathing to positively influence ER (Arch & Craske, 2006;Obradović et al, 2021;Zhang et al, 2019). The question that needs to be answered is how parents can teach such skill effectively.…”
Section: Slow-deep Breathingsupporting
confidence: 72%
See 2 more Smart Citations
“…Deep breathing is a valuable skill that parents can teach their children to help them manage their emotions and facilitate an SRS for optimal EC. Using deep breathing connects well with previous studies on the significance of deep breathing to positively influence ER (Arch & Craske, 2006;Obradović et al, 2021;Zhang et al, 2019). The question that needs to be answered is how parents can teach such skill effectively.…”
Section: Slow-deep Breathingsupporting
confidence: 72%
“…The findings of experts' interviews report that deep breathing has the potential to teach anger regulation through playful interaction used daily with repetition. Similarly, existing studies have investigated teaching children deep breathing exercises through a picture book (Morgado, 2011) or through watching a video (Obradović et al, 2021). It was demonstrated that teaching children deep breathing exercises helped them calm down and decreased their physiological arousal by using visual, tactile, and narrative cues to support their learning.…”
Section: Deep Breathing For Anger Regulation Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has shown that both resting RSA and sleep can also be adjusted with intervention. Specifically, interventions that include biofeedback (Dormal et al, 2021) or deep breathing (Obradović et al, 2021), have both been associated with an increase in resting RSA. High levels of sleep problems were detected among college students in the present study and in others (e.g., Acharya et al, 2018; Liu et al, 2021), and sleep hygiene education programs are associated with improvements in students’ sleep (Brown et al, 2006; Hershner & O'Brien, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to calm down quickly and restore mental clarity is critical for dealing with emergencies and making life-saving decisions [37][38][39]. Furthermore, reducing the intensity of fear and improving the ability of survivors and first responders to stay calm, sleep, and restore energy reserves may reduce the risk of later developing PTSD [4,45,46].…”
Section: Polyvagal Theorymentioning
confidence: 99%